The writing and the dance movement as a way of subjective inscription in adolescence - Molina Ovares, Andrea (2021)
This article carries out a psychoanalytic analysis of the creative progress and artistic works made by a group of adolescents from the región of San Ramón in dance and  writing spaces. It concludes that the artistic creation enables adolescents to think and elaborate their own discourse, contributing to the subjective construction of individual and collective forms. In addition, the speeches on death, suicide and tragedy call for a stop to treat these issues as a taboo.